Interleukin-6 in Allogeneic Stem Cell Transplantation: Its Possible Importance for Immunoregulation and As a Therapeutic Target - Tvedt, Tor Henrik Anderson; Ersvaer, Elisabeth; Tveita, Anders Aune; Bruserud, Øystein (Frontiers in Immunology, 2017)
Abstract Allogeneic stem cell transplantation is associated with a high risk of treatment-related mortality mainly caused by infections and graft versus host disease (GVHD). GVHD is characterized by severe immune dysregulation and impaired regeneration of different tissues, i.e. epithelial barriers and the liver. The balance between pro and anti-inflammatory cytokine influences the risk of GVHD. IL-6 is a cytokine that previously has been associated with pro-inflammatory effects. However, more recent evidence from various autoimmune diseases (e.g. inflammatory bowel disease, rheumatoid arthritis) has shown that the IL-6 activity is more complex with important effects also on tissue homeostasis, regeneration and metabolism. This review summarizes the current understanding of how proinflammatory IL-6 effects exerted during the peritransplant period shapes T-cell polarization with enhancement of Th17 differentiation and suppression of regulatory T-cells, and in addition we also review and discuss the results from trials exploring non-selective IL-6 inhibition in prophylaxis and treatment of GVHD. Emerging evidence suggests that the molecular strategy for targeting of IL-6 initiated intracellular signaling is important for the effect on GVHD. It will therefore be important to further characterize the role of IL-6 in the pathogenesis of GVHD to clarify whether combined IL-6 inhibition of both trans (i.e. binding of the soluble IL-6/IL6 receptor complex to cell surface gp130) and cis signaling (i.e. IL-6 ligation of the IL-6 receptor/gp130 complex) or selective inhibition of trans signaling should be tried in the prophylaxis and/or treatment of GVHD in allotransplant patients.